Cochlear Implantation in the United Arab Emirates: Otolaryngologists’ Knowledge, Attitudes, and Practices - Muhammed Ayas; Ahmad Al Amadi; Ahmad Al Shamsi; Jameel Muzaffar; Manohar Bance (Audiology Research)
Background: Cochlear implants (CIs) are the gold standard intervention for severe-to-profound sensorineural hearing loss. Their success depends not only on technological advancements but also on the knowledge, attitudes, and practices (KAP) of otolaryngologists responsible for patient selection, counselling, and postoperative management. Objective: This study aimed to evaluate the KAP of otolaryngologists in the UAE towards CIs, identify gaps in training and decision-making, and assess adherence to global CI protocols. Methods: A cross-sectional study was conducted using a self-administered online questionnaire distributed to otolaryngologists across public and private healthcare institutions in the UAE. The survey assessed demographics, clinical knowledge, attitudes towards CIs, and clinical practices. Descriptive and inferential statistical analyses were performed to assess the relationships among knowledge levels, referral frequency, and institutional factors. Results: A total of 31 otolaryngologists participated. While 74% demonstrated moderate-to-high knowledge of CIs, 39% had low awareness of national guidelines. Most (61%) strongly supported CI integration into treatment protocols, but financial and institutional barriers were frequently cited as challenges. Knowledge levels significantly correlated with referral frequency (p < 0.001), indicating a gap between awareness and practice. Conclusions: This is the first study in the UAE assessing otolaryngologists’ KAP regarding CIs. Despite favourable attitudes, limited guideline awareness, financial barriers, and inconsistent multidisciplinary collaboration remain challenges. Targeted clinician education, standardised CI guidelines aligned with international benchmarks, and improved funding mechanisms are essential to enhance CI accessibility and optimise patient outcomes in the region.